Impact Transformation of Merit System in Civil Servant Selection System to Quality of Governance - Fadilla Fadilla; Lina Miftahul Jannah; Muh Aziz Muslim (Asian Journal of Management, Entrepreneurship and Social Science, 2024)
This research aims to analyse research developments related to merit-based recruitment. Bibliometric analysis was used to determine the dynamics of research topics related to merit-based recruitment using the Scopus database until from January 2002 to October 2023 using 159 filtered articles as a basis for conducting a systematic review. Despite article growing slowly from 2002 to 2014, in recent years the research has significantly expanded. From 2014 to 2023, every year 7-17 articles are published, meanwhile, before 2014, research each year only produced 3-5 articles or even none at all. In terms of citation, the article published from 2004 to 2018 most cited. Article of Dahlstorm, Lapuente, and Teorell (2012) was the highest citation document and become a significant article to referenced about merit-based recruitment. The findings show based on systematic review that merit-based recruitment is are strongly associated with higher to government quality. Mapping indicates the factors affecting government quality include public service motivation, integrity, motivating factors, organizational compliance, workforce diversity, political consideration, efficiency management, level of expertise of administration personnel, innovative learning. Meanwhile, merit-based recruitment is strongly associated to lower political settlement, patron-client relationship, corruption, and nepotism. Also, from the systematic review, the selection methods include written exams and interviews based on criteria including educational qualifications, training and relevant work experience.